Analysis of the domestic market of compressor and ultrasonic nebulizers - T. S. Brytanova; A. V. Samko (Zaporozhye State Medical University, 2022)
The aim of the work is to organize informational files about compressors and ultrasonic nebulizers determination of actuality and availability in marketing analysis of the domestic market. Materials and methods. Data from the Apteka.UA and the official website of Tabletki.ua were used to analyze the brand and assortment structure of ultrasonic and compressor nebulizers. The search analytical, systematic, comparative, and statistical methods and methods of mathematical and logical analysis were used in the work. Results. The analysis of the market of assortment and brand structures of the compressor and ultrasonic nebulizers was carried out. The obtained results showed the presence on the market of 16 manufacturers from 10 countries in the world of compressor nebulizers and 9 manufacturers from 7 countries in the world of ultrasonic nebulizers. Among them, the largest suppliers were identified, such as Omron Healthcare (Japan) and LLC Medhouse Swiss GmbH (Ukraine). The calculated stress coefficient indicated greater competition between compressor manufacturers (Kvi = 0.94) compared to ultrasonic (Kvi = 0.88) nebulizers. The level of monopolization was determined using the Herfindahl-Hirschman index. The results indicated a moderately concentrated market for both types of nebulizers. Analysis of socio-economic affordability by indicators of price liquidity ratio and solvency adequacy noted low availability of this group of goods for consumers of pharmacies. Conclusions. The results of the company structure research indicated the vast majority of manufacturers of foreign companies and a wide range of both ultrasonic and compressor nebulizers. In the course of the work, the available commodity positions in pharmacies in Ukraine were investigated. According to the calculations of the coefficient of tension and the level of monopolization. It was possible to determine the competitiveness among manufacturing firms. The results of the assessment of the liquidity ratio and the adequacy of solvency made it possible to assess the purchasing power of the population in this group of goods.